Development and validation of an inventory to evaluate the implementation of main educational elements in promoting higher-order thinking skills - Che Md Ghazali Nor Hasnida, Mat Rabi Norfishah, Md Hassan Nurul Huda, (Universiti Pendidikan Sultan Idris, 2017)
Development and validation of an inventory to evaluate the implementation of main educational elements in promoting higher-order thinking skills by Che Md Ghazali Nor Hasnida, Mat Rabi Norfishah, Md Hassan Nurul Huda,